Data Mining Using Support Vector Machine Model for Baturraden Tourism Visitor Satisfaction Prediction - Damayanti, Suci; Oktaviana, Luzi Dwi; Bratakusuma, Trias (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The tourism industry is a significant economic sector and a driver of local and national economic growth. Tourism not only contributes economically, but also plays an important role in introducing and preserving the cultural and natural wealth of an area. One of them is Baturraden tourism, a tourist destination located in Indonesia is experiencing a rapid increase in the number of tourist visits. Baturraden is a tourist destination located in the highlands at the foot of Mount Slamet, Indonesia, precisely in Banyumas Regency, Baturraden District. Tourists who visit every year are increasing but tour managers have not realized whether the tourists are satisfied or not so research is needed to measure the level of satisfaction of tourists so that the Baturraden tourism is better. To measure the level of satisfaction, an algorithm is needed, in this study the algorithm used is a support vector machine (SVM) to collect data that will be used as a dataset by taking reviews on google maps manually then the data is grouped into groups of satisfied and dissatisfied tourists, as many as 100 data are taken and processed. So that the final result obtained an accuracy value of 86.00%, and for reviews tend to be positive or satisfied tourists visiting the baturaden tourist area.